DRM or No DRM for Digital Music Lovers and Sellers - Paul, Vivek; Sharma, Vandana; Vijayran, Manisha (Gyan Management Journal, 2010)
Online musc is encrypted under DRM and then sold. DRM refers to technolo9y based systems which are used for the management of copyright material and the terms of their usage. DRM is digital rights management where in the copyri9ht owner allows its digital content to be shared on the digital services, terminating across pc and mobile and earns revenue in each transaction via a billing model. DRM is an effective tool to combat illegal distribution of audio/ music, videos, games, computer software, pictures, text, data and books/ literary works. The case discusses the DRM concept and its evolution for the prevention of illegal distribution and duplication of digital data. The case gives a brief note on some companies that made use ofDRM and its related technologies for safeguarding their digital content. It gives a global purview on how Apple and Windows will be the biggest players in this segment. It then focuses on challenges that DRM faces in the restricted environments in which it operates and does not allow interoperability across pc, mobile and mp3 players. The case also talks of how these problems can be overcome and the stategies, henceforth, for its success. The case ends with a discussion on the road ahead for D RM, its latest developments.
Keywords: DRM; technology; management; software,; pictures; books/ literary